2017
DOI: 10.1136/bmjopen-2017-017172
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic validity of early-onset obsessive-compulsive disorder in the Danish Psychiatric Central Register: findings from a cohort sample

Abstract: ObjectivesEmploying national registers for research purposes depends on a high diagnostic validity. The aim of the present study was to examine the diagnostic validity of recorded diagnoses of early-onset obsessive-compulsive disorder (OCD) in the Danish Psychiatric Central Register (DPCR).DesignReview of patient journals selected randomly through the DPCR.MethodOne hundred cases of OCD were randomly selected from DPCR. Using a predefined coding scheme based on the Children’s Yale Brown Obsessive Compulsive Sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 20 publications
1
19
1
Order By: Relevance
“…It could also be explained by Danish clinicians gaining more experience in using the ICD-10 criteria that were implemented in 1994. In contrast to the present study, studies examining the validity of hyperkinetic disorder 20 and OCD 19 diagnoses did not find a time trend in diagnostic validity. This difference might be caused by different analytical methods (dichotomous time variables in the hyperkinetic disorder study vs. a continuous time variable in the present study).…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…It could also be explained by Danish clinicians gaining more experience in using the ICD-10 criteria that were implemented in 1994. In contrast to the present study, studies examining the validity of hyperkinetic disorder 20 and OCD 19 diagnoses did not find a time trend in diagnostic validity. This difference might be caused by different analytical methods (dichotomous time variables in the hyperkinetic disorder study vs. a continuous time variable in the present study).…”
Section: Discussioncontrasting
confidence: 99%
“…23 However, validity has been reported to be slightly higher for other child and adolescent psychiatric diagnoses in the DPCRR. The validity of early-onset obsessive-compulsive disorder (OCD) diagnoses was found to be 85% 19 and that of hyperkinetic disorder was 86.8%. 20 Another study validating the diagnosis of childhood autism reported a validity of 94% with even 97% meeting the criteria for any autism spectrum disorder (ASD).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the Danish national healthcare system provides psychiatric care to all citizens at no cost, and this structure supports broad inclusion of the clinical population within the registries, those with subthreshold clinical disorders or those who do not seek treatment would not be included herein. Although the validity for childhood autism, schizophrenia and OCD in Danish registers is over 90%, [73][74][75] and 83% for ADHD, 76 TS/CT diagnoses have yet to be validated. Of note, such validation has been achieved in a similar Swedish health care system 77 .…”
Section: Accepted Manuscriptmentioning
confidence: 99%